Implementasi Event Tree Analysis dan metode Andersen untuk penilaian risiko Bendungan Titab - Dea Putri Arifah; Dyah Ari Wulandari; Hari Nugroho (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Dam as water resources infrastructure has inherent failure risks, necessitating regular risk assessments to ensure its safety and functional sustainability. This study aims to evaluate the risk level of Titab Dam using two main methods: Event Tree Analysis (ETA) and the modified Andersen method. Hazard identification was conducted based on the 2024 inspection report, followed by failure mode analysis using FMECA (Failure Mode, Effects, and Criticality Analysis) to determine mitigation priorities. ETA results revealed that both individual and group extreme probabilities exceeded tolerance limits, requiring special interventions for several primary components, especially at the dam crest. Meanwhile, the assessment using the Andersen method produced a safety score of 66.33, categorized as ADEQUATE and still requiring corrective measures for defects found during inspections. This research provides an integration of two methods (ETA and Andersen) to strengthen the validation of dam risk assessment in Indonesia, thereby making the safety evaluation results more comprehensive and reliable. This study emphasizes the importance of implementing risk assessments as part of major inspections and ongoing monitoring activities to minimize failure potential and improve dam safety.